2022
DOI: 10.1093/gji/ggac391
|View full text |Cite
|
Sign up to set email alerts
|

Empirical H/V spectral ratios at the InSight landing site and implications for the martian subsurface structure

Abstract: Summary The H/V spectral ratio inversion is a traditional technique for deriving the local subsurface structure on Earth. We calculated the H/V from the ambient vibrations at different wind levels at the InSight landing site, on Mars, and also computed the H/V from the S-wave coda of the martian seismic events (marsquakes). Different H/V curves were obtained for different wind periods and from the marsquakes. From the ambient vibrations, the recordings during low-wind periods are close to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 89 publications
(118 reference statements)
2
14
0
Order By: Relevance
“…Below this, velocities increase again, but remain lower than in the Amazonian lavas, which could indicate a more physically or chemically weathered basaltic unit. These layered models down to 100 m depth are compatible with the lower-resolution compliance data (Carrasco et al 2022).…”
Section: Subsurfacesupporting
confidence: 79%
See 1 more Smart Citation
“…Below this, velocities increase again, but remain lower than in the Amazonian lavas, which could indicate a more physically or chemically weathered basaltic unit. These layered models down to 100 m depth are compatible with the lower-resolution compliance data (Carrasco et al 2022).…”
Section: Subsurfacesupporting
confidence: 79%
“…Assuming Rayleigh waves as the main component of the ambient background wavefield, the H/V inversion revealed several layers with altering high and low velocities. Subsequent analysis focused on the S-wave coda of marsquakes (Carrasco et al 2022), since the ambient wavefield could be biased by amplitudes close to the instrument self-noise for periods of low wind and the influence of lander modes for higher winds (Mahvelati & Coe, 2021, Xio & Wang 2022. In the 0.4-10 Hz bandwidth, an additional H/V peak around 8 Hz was found and inverted with a diffusive wave field approach, i.e.…”
Section: Subsurfacementioning
confidence: 99%
“…To carry out this task, different approaches have been employed. The seismic studies have revealed that the uppermost 100–200 m beneath the landing site are composed of two low‐velocity zones (∼0–20 m and ∼30–80 m) and two high‐velocity zones (∼20–30 m, and ∼80–200 m) (Carrasco et al., 2022; Hobiger et al., 2021; Kenda et al., 2020). The low‐velocity zones are interpreted as brecciated regolith and sediments, while the high‐velocity zones represent basaltic layer based on in situ geological investigations (Warner et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The high corner frequency (several Hz) indicates a short source duration, consistent with a hypervelocity impact. The tell-tale signature of the VF events in the seismic record is a strong horizontal motion at frequencies above 5 Hz (Clinton et al 2021), which has been explained by a local resonance effect (Carrasco et al 2023) (for a spectral comparison of a HF and VF event see Fig. S2).…”
Section: Vf Frequency Content and Envelopesmentioning
confidence: 99%